Level of agreement between laboratory and non-laboratory instruments in cardiovascular risk stratification (Research, Society and Development, 2024)
Objective: To evaluate the degree of agreement between the Framingham Cardiovascular Risk Score and the HEARTS program calculator, in its version using BMI, in stratifying Cardiovascular Risk (CVR) in diabetic and/or hypertensive patients in Primary Health Care (APS). Methodology: Cross-sectional, exploratory and epidemiological study, with a convenience sample of 89 individuals selected from 10 Basic Health Units in a medium-sized Brazilian municipality. The scores were applied to the patients and the degree of agreement was analyzed using the Kappa Coefficient. Bivariate analysis of independent variables was performed using Chi-Square. Results: In the studied population, there was a predominance of “high” risk ranges (>10%), for both sexes in both scales. The HEARTS calculator showed low discrimination power for patients with higher cardiovascular risks (>10%). The bivariate analysis showed a positive relationship between the geriatric age group, high blood pressure and the presence of hypertension in women with higher CVR in the ERG, but did not find correlations in the HEARTS. The Kappa agreement index between the two scores was 0.06. Conclusion: There was minimal agreement between the scores, in addition to a different behavior in relation to the criteria used to calculate the CVR. It is important to encourage national studies to calibrate and validate RCV calculators that correspond to the Brazilian reality, in order to make facilitating tools for calculating RCV in PHC accessible.